Clinical characteristics and treatment outcomes of diffuse large B‐cell lymphoma involving the eye and ocular adnexa in East Asia. Issue 7 (9th January 2021) - Han, Sun Hyup; Kim, Yoon‐Duck; Jang, Jaeho; Park, Ji Woong; Young, Stephanie M; Woo, Kyung In
Abstract: Purpose: To investigate the clinical features and outcomes of diffuse large B‐cell lymphoma (DLBCL) involving the eye and ocular adnexa in an East Asian population and emphasize the importance of prompt biopsy and treatment in unusually progressive ocular adnexal DLBCL for better visual outcomes. Methods: Retrospective case series of 38 patients diagnosed with DLBCL involving the eye and ocular adnexa between 1995 and 2018 at a single tertiary institution. Results: There were 38 patients (22 men, 16 women), 22 (57.9%) of which had ocular adnexal lymphoma (OAL) and 16 (42.1%), vitreoretinal lymphoma (VRL). The OAL group showed higher rates of unilateral involvement (p = 0.01) and localized disease presentation (p = 0.01). Thirteen (59.1%) of 22 OAL patients were primary diseases and 9 (40.9%) were secondary. Between primary and secondary OAL groups, there was no statistical difference in clinical characteristics such as age, gender and laterality (p = 0.47, p = 0.19 and p = 0.66, respectively). All secondary OAL cases were either disseminated or relapsed by definition and only two cases (15%) of primary OAL showed disseminated presentation (p < 0.01). Six (37.3%) of 22 OAL patients showed a rapid decrease in visual acuity within 15 days and the visual recovery was irreversible in 3 of them. Conclusion: OA‐DLBCL has a grave prognosis and its visual outcomes largely depend on the timing of diagnosis and treatment. When a high‐grade lymphoma is suspected, prompt biopsy and treatment should be performed to ensure optimal visual, clinical and survival outcomes.